Objective evaluation of orbito-zygomatic reconstruction with scapular tip free flaps to restore facial projection and orbital volume. (June 2021) - Sahovaler, Axel; Chan, Harley H.L.; Ferrari, Marco; Gualtieri, Tommaso; Zhang, Charlotte; Taboni, Stefano; Irish, Jonathan C.; Gilbert, Ralph W.
Highlights: Orbito-zygomatic reconstruction is critical in facial contour and orbit position. Contour and shape restoration were adequately achieved with scapular tip flaps. There were no significant differences in orbital volume postoperatively. Scapular tip flaps are a valuable option in dealing with orbito-zygomatic defects. Abstract: Background: Restoring anatomical contour and position of the malar eminence and orbital rim following ablative mid-face procedures is critical in maintaining facial contour and orbit position. Objective: To report our reconstructive approach using the scapular tip free-flap (STFF) for orbito-zygomatic defects, evaluating contour and overall shape restoration. Methods: The study included 2 series: a clinical cohort of 15 consecutive patients who underwent an orbito-zygomatic reconstruction with a STFF and a cohort of 10 patients who had CT scan imaging but did not have orbito-zygomatic surgical resection or reconstruction. Using a 3D software, overall conformance (OC) and contour conformance (CC) with respect to the mirrored contralateral (clinical cohort) or native zygoma (preclinical cohort) were analyzed. Postoperative orbital volumes were also measured in the clinical cohort. Mean, median, root-mean-square (RMS), minimum and maximum measurements were obtained both for OC and CC. Conformance values of clinical and preclinical cohort were compared to objectively evaluate the quality of reconstruction in terms of orbito-zygomatic framework restoration (Mann-Whitney test). Results: All measurements for OC and CC between scapular tip and the zygoma showed no differences, both on the clinical (RMS: OC 3.29 mm vs CC 3.32 mm -p = NS-) and preclinical (RMS: OC 2.03 mm and CC 2.31 mm -p = NS-) cohorts. Moreover, there were no differences in post-operative orbital volumes in the clinical cohort. Clinical outcomes of the case-series are also reported. Conclusion: The STFF is highly effective in restoring facial projection and orbital volume in orbito-zygomatic reconstruction.